Pyridothiadiazine derivatives as aldose reductase inhibitors having antioxidant activity. (1st November 2016) - Zhu, Shaojuan; Zhang, Shuzhen; Hao, Xin; Qin, Xiangyu; Parveen, Shagufta; Yang, Shaoqi; Ma, Bing; Zhu, Changjin
Abstract: A series of aldose reductase (ALR2) inhibitors based on pyridothiadiazine were prepared and evaluated for their activities in ALR2 inhibition, DPPH scavenging, and MDA inhibition. Comparison studies were carried out between analogs having either hydroxyl or methoxy groups substituted on the N2-benzyl side chains of the compounds. Most of the hydroxy-substituted compounds were found to be more potent compared to their methoxy-substituted analogs with respect to DPPH inhibition (>93%) and MDA inhibition (>73%). However, ALR2 inhibitory activity was found to be affected by the electron-withdrawing substituent at the C7 position in addition to the effect of the N2-substituted benzyl group. These results provide an array of multifunctional ALR2 inhibitors possessing capacities both for ALR2 inhibition and as antioxidants.